2018
DOI: 10.1021/acssuschemeng.7b03964
|View full text |Cite
|
Sign up to set email alerts
|

Stainless Steel Scrubber: A Cost Efficient Catalytic Electrode for Full Water Splitting in Alkaline Medium

Abstract: Sometimes, searching for a cost efficient bifunctional catalytic material for water splitting can be accomplished from a very unlikely place. In this work, we are reporting such a discovery of utilizing the stainless steel (SS) scrubber directly as a catalytic electrode for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) of water electrolysis in 1 M KOH. The iR corrected overpotential calculated at an areal current density of 10 mA cm–2 for a SS scrubber in HER is 315 mV which is 273 mV h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 57 publications
3
51
0
Order By: Relevance
“…A Nyquist plot of stainless steel scrubber (316 L) acquired at an OER overpotential of 300 mV in 1.0 M KOH from our earlier study is given as an example that fits with the simple Randle's cell shown below . The resultant Nyquist plot take a shape of a depressed semi‐circle as shown in Figure .…”
Section: Electrochemical Impedance Spectroscopy: the Basics Within Thmentioning
confidence: 99%
See 1 more Smart Citation
“…A Nyquist plot of stainless steel scrubber (316 L) acquired at an OER overpotential of 300 mV in 1.0 M KOH from our earlier study is given as an example that fits with the simple Randle's cell shown below . The resultant Nyquist plot take a shape of a depressed semi‐circle as shown in Figure .…”
Section: Electrochemical Impedance Spectroscopy: the Basics Within Thmentioning
confidence: 99%
“…To avoid this, several materials have been reported to be catalyzing these half‐cell reactions with relatively lower overpotentials. These include noble and precious metals (Pt, Ir, and Ru) and their oxides, non‐precious metals (Mn, Fe, Co, Ni, Cu, V, Ti, Mo, W, and Re) and their compounds and non‐metallic carbonaceous materials . Due to the cost concerns of utilizing noble and precious metals, non‐precious metals based materials are being investigated intensively for electrocatalytic water splitting in recent days.…”
Section: Introductionmentioning
confidence: 99%
“…However, the elemental compositions of SS are more complex, generally containing the elements of Fe, Ni, Cr, and Mn, which result in the complicated compositions and abundant controllability for SS‐based electrocatalysts. [ 166–168 ] SS not only has the similar advantages to the aforesaid alloys of high electrical conductivity, porous structure and high specific surface area, but also exhibits remarkable corrosion resistance at harsh conditions. [ 169 ] The corrosion resistance produces the difficulty of achieving efficient electrocatalysts by corrosion engineering, but simultaneously endows SS with high durability for electrocatalysis.…”
Section: Corrosion Engineering Enabled Electrocatalystsmentioning
confidence: 99%
“…One of the promising approaches to address the tendency of the catalysts peeling off from the substrates is fabricating self-supporting electrocatalysts. 38 On the race to accomplishing the abovementioned approach, the stainless steel mesh (SSM) especially the 304-, 316-, and AISI 304-type has attracted great attention 38,4042 not only due to its low cost but also its chemical stability in the alkaline environment. 4345 SSM has shown impressive performance as an OER electrocatalyst in its pristine form 37,38 and significant performance enhancement upon different facile surface modification or exfoliation methods to improve its surface area.…”
Section: Introductionmentioning
confidence: 99%